2022
DOI: 10.1177/25158414221083374
|View full text |Cite
|
Sign up to set email alerts
|

Ocular manifestations of COVID-19

Abstract: COVID-19 is a disease caused by a SARS-CoV-2 viral infection, a disease that was first detected in December 2019 in Wuhan, Hubei Province, China. COVID-19, formerly known as 2019 Novel Coronavirus (2019-nCoV) respiratory disease, was officially named COVID-19 by the World Health Organization (WHO) in February 2020. By 25 May 2021, there were 33,579,116 confirmed cases with 599,109 COVID-19 deaths worldwide. The purpose of this review article is to provide an update on what is currently known about COVID-19 ocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 88 publications
0
24
1
Order By: Relevance
“…In addition, the development of optic neuritis, disc edema, vascular tortuosity, acute macular neuroretinopathy (AMN), retinal occlusive vasculopathy (RVO), retinal artery occlusion, intraretinal hemorrhages, cotton wool, uveitis, and endogenous endophthalmitis has been reported in patients who tested positive and had moderate to severe COVID-19 symptoms. Often these diseases affecting the retina and retinal vasculature are the subject of single-case studies so it is necessary to expand these investigations in order to test the incidence of ocular complications of COVID-19 on a large scale [23].…”
Section: Ocular Complications From Coronavirus Infectionsmentioning
confidence: 99%
“…In addition, the development of optic neuritis, disc edema, vascular tortuosity, acute macular neuroretinopathy (AMN), retinal occlusive vasculopathy (RVO), retinal artery occlusion, intraretinal hemorrhages, cotton wool, uveitis, and endogenous endophthalmitis has been reported in patients who tested positive and had moderate to severe COVID-19 symptoms. Often these diseases affecting the retina and retinal vasculature are the subject of single-case studies so it is necessary to expand these investigations in order to test the incidence of ocular complications of COVID-19 on a large scale [23].…”
Section: Ocular Complications From Coronavirus Infectionsmentioning
confidence: 99%
“…Early in the COVID-19 pandemic it was also noted that many patients, during or after COVID-19 infection over the "short term" complain of a general malaise and extra-respiratory neurological symptoms including confusion, delirium, headache, mental and psychiatric disorders, disorders in mood (depression and dysthymic disorder), disturbances in sleep (insomnia), cognitive and memory impairment, "brain fog", deficiency in smell (anosmia) or taste (ageusia), muscle weakness and myalgia, sensorimotor deficits, dysautonomia as well as convulsions and/or peripheral neuropathies that include Bell's palsy and peripheral neuropathies with pain (Gupta and Jawanda, 2022;Lingor et al, 2022;Stefanou et al, 2022). COVID-19 associated ocular manifestations have been also documented to include a wide range of ophthalmic symptoms associated with eye irritation (chemosis), conjunctivitis, conjunctival hyperemia, anterior uveitis, retinitis, and optic neuritis and in advanced COVID-19 infection with visual and perception disturbances including visual disorientation and hallucinations, especially in elderly COVID-19 patients (Hill et al, 2021;Hixon et al, 2021;Lin et al, 2021;Reinhold et al, 2021;Al-Namaeh, 2022;Lukiw, 2022a,b). Accumulating evidence indicates an especially high prevalence of prolonged neurological symptoms among COVID-19 survivors and most of these afflictions and neurological disruptions persist as the long-term neurological sequelae of COVID-19 also known as "long COVID" or "post-COVID-19 syndrome" (Nepal et al, 2020;Song et al, 2020;Ahmed et al, 2022;Sanyaolu et al, 2022;Visco et al, 2022; Figure 1).…”
Section: Sars-cov-2 -The Short-and Long-term Neurological Sequelaementioning
confidence: 99%
“…A European multicenter study reported that about 12% of patients had ageusia and anosmia as early symptoms [ 75 ]. Ocular manifestations are often non-specific, and conjunctivitis, mainly manifested as redness, watering, discharge and foreign body sensations, is the most frequently reported; other ocular complications include dry eye, blurred vision, ocular pain, photophobia and itchiness [ 76 ]. Notably, ocular signs and symptoms were the initial presentations in 3.3% of COVID-19 patients [ 76 ].…”
Section: Extrapulmonary Manifestations and The Role Of Gut Microbiota...mentioning
confidence: 99%
“…Ocular manifestations are often non-specific, and conjunctivitis, mainly manifested as redness, watering, discharge and foreign body sensations, is the most frequently reported; other ocular complications include dry eye, blurred vision, ocular pain, photophobia and itchiness [ 76 ]. Notably, ocular signs and symptoms were the initial presentations in 3.3% of COVID-19 patients [ 76 ]. Dermatological manifestations have been observed in 2–20% of patients [ 77 , 78 ].…”
Section: Extrapulmonary Manifestations and The Role Of Gut Microbiota...mentioning
confidence: 99%